KETERAMPILAN BELAJAR DAN BERINOVASI ABAD 21 PADA ERA REVOLUSI INDUSTRI 4.0 - Putu Eka Sastrika Ayu (Purwadita : Jurnal Agama dan Budaya, 2019)
Fundamentaly, industrial revolution 4.0 can change our way of life, work and relationamong us. One of the govermet effects in order to enhance student comprehension in facing theindustrial revolution 4.0 is to revitalize curriculum in to so called K13 national curriculumwitch adapted from 21st century’s eduction concept. The 21st century competeciens demind ofeducation word to integrated knowledge comprehension skill and attitude as well as ablity oninformation and communication technologi. Our education world was to required to bad studentin order to face global threats. There are three core subjects of the 21st centurys educationnamely: (1) life and career skills, (2) learning and innovation skills, (3) information, medias andskills. Specially in case of leaning and innovation skills there are some aspects, namely: (1)critical thingking and problems solving: students be able to use various reasons such as inductiveor deductive reasons in varians situations to use way of thingking system, to make decision andto solve problems; (2) communication and collaboration: student be able to communicationeffectively and to collaborate with ather grup member; (3) creativity and innovation: studentsbe able to conduct creative thinking and working creatively.